PELAKSANAAN PROGRAM BIMBEL LITERASI EKONOMI SEDERHANA SEBAGAI UPAYA EDUKASI PADA ANAK SEKOLAH DASAR (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Simple Economic Literacy Tutoring Program for children in Rejo Mulyo Hamlet was initiated in response to the low level of understanding among children regarding basic economic concepts that are closely related to their daily lives. Many children are still unfamiliar with various professions, the process of earning money through work, and the distinction between goods and services. This lack of early exposure often causes them to perceive econom ic activities as distant and difficult to comprehend. To address this issue, the program was implemented as a nonformal educational initiative using fun, simple, and contextual learning methods such as storytelling, drawing, and interactive discussions. Through these activities, children were encouraged to imagine their dream jobs, think critically, and relate economic concepts to their real-life experiences. The results show that the program successfully enhanced children’s curiosity, understanding of economic roles, and positive attitudes toward economic activities in their surroundings. Overall, this initiative demonstrates that early economic literacy education can strengthen children’s foundational knowledge and life skills, supporting their readiness for future learning and social development